The 4 phases of evolution of political communication systems: from the golden age of the parties to the golden age of the users - Tasente, Tanase (Technium Social Sciences Journal, 2021)
The political media communication system began to develop, in a first phase, in the first two decades after the Second World War, this period being called by Blumler and Kavanagh (1999) as "the golden age of the parties" or as “the age of the newspapers”. In the 1960s, a new stage in the evolution of political communication systems began, when few national televisions put a monopoly on the media market, becoming the dominant medium in which political communication unfolded. This stage was named "the television era" or "the modern period of electoral campaigns". Two new aspects to the previous period of evolution are due to the diminution of the voters’ loyalty and trust towards the political parties and the shift from direct communication to prime-time communication. The third phase of the evolution of political communication systems began to take shape at the end of the 20th century and the beginning of the 21st century and was called the "postmodern period" or "digital era". Major changes in this period of political communication development have occurred both in technology, consumer behavior of voters, and in communication strategies. After 1990, for many other democratic countries and after 2000, for other totalitarian countries, political communication has undergone a strong transformation into its three points: (1) changing the communication channel and its characteristics far different from classical means, (2) related to the content of the message and the political discourse and, perhaps, the most important aspect (3) the public’s ability to actively participate in government acts or protest actions challenging government acts.